2011
DOI: 10.1038/ajg.2011.231
|View full text |Cite
|
Sign up to set email alerts
|

Fecal HMGB1 Is a Novel Marker of Intestinal Mucosal Inflammation in Pediatric Inflammatory Bowel Disease

Abstract: It was shown for the first time in our study that HMGB1 is secreted by human inflamed intestinal tissues and abundantly found in the stools of IBD patients. Hence, it can be considered as a novel marker for intestinal inflammation. We can also suggest that the presence of HMGB1 in large amounts in the fecal stream of IBD patients is mainly due to active secretion of the protein stored in the nucleus rather than a "de novo" synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 42 publications
4
79
0
2
Order By: Relevance
“…Furthermore, HMGB1 antagonism using anti-HMGB1 antibody or ethyl pyruvate ameliorates colitis in the DSS and Il10 -/-mouse models, respectively (7,8). Very little is known about HMGB1 in human IBD, just that children with IBD have increased levels of this protein in their feces (9). These data reflect the fact that the majority of HMGB1 research has focused on its extracellular functions during inflammation, despite it being concurrently found in the cell cytosol under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, HMGB1 antagonism using anti-HMGB1 antibody or ethyl pyruvate ameliorates colitis in the DSS and Il10 -/-mouse models, respectively (7,8). Very little is known about HMGB1 in human IBD, just that children with IBD have increased levels of this protein in their feces (9). These data reflect the fact that the majority of HMGB1 research has focused on its extracellular functions during inflammation, despite it being concurrently found in the cell cytosol under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of neutralizing antibody against HMGB1 or blockade by soluble RAGE was also shown to be effective in various organ injuries such as acute lung injury, ischemia-reperfusion hepatic injury or rheumatoid arthritis [33,34,35]. Recently, it was shown that HMGB1 is secreted by human inflamed intestinal tissues and is abundantly found in the stool of patients with IBD [36]. It was also shown that HMGB1 B box increases the permeability of Caco-2 enterocytic monolayers and impairs intestinal barrier function in mice [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, cytoplasmic HMGB1 levels increased significantly in inflamed tissue. Because HMGB1 is constitutively expressed in the nuclei of almost all eukaryotic cells and transfers to the cytoplasm during inflammation, the authors considered increased fecal HMGB1 to come from active secretion of protein stored in the nucleus rather than ''de novo'' synthesis [47]. However, it was not determined whether HMGB1 nuclear-cytoplasmic transfer would affect its normal intra-nuclear function.…”
Section: Hmgb1 and Ibd Expression Of Hmgb1 In Ibdmentioning
confidence: 99%
“…Similarly, HMGB1 is abundantly present in the feces of pediatric IBD patients [47]. The amount of fecal HMGB1 correlated with mucosal inflammation (even subclinical) and healing, indicating the potential usefulness for HMGB1 in monitoring disease progression and assessing therapeutic outcomes in IBD patients [48].…”
Section: Hmgb1 and Ibd Expression Of Hmgb1 In Ibdmentioning
confidence: 99%